Effect of Vitamins A, E, C and Omega-3 Fatty Acids on Lipid Peroxidation in Streptozotocin Induced Diabetic Rats - SH Fakher; M Djalali; SMB Tabei; H Zeraati; E Javadi; MR Sadeghi; E Mostafavi; F Fatehi (Tehran University of Medical Sciences, 2007)
Background: To assess the effect of supplementation with vitamins A, E and C and ω-3 fatty acids on lipid peroxidation in strepto¬zotocin (STZ) induced diabetic rats. Methods: Sixty four male wistar rats weighting 250g were divided into four groups as normal control, diabetic control, dia¬betic with vitamin A, E as well as C supplementation and diabetic with ω-3 fatty acids supplementation. After four weeks of treat¬ment the rats were anesthetized and malondialdehyde (MDA) levels were investigated in blood samples, liver and heart ho¬mogenate. Results: In diabetic rats MDA level in plasma, liver and heart was significantly more elevated than normal control rats (P< 0.05). Vitamin A, E and C supplementation caused significant decrease in plasma, liver and heart MDA (P< 0.05). A signifi¬cant decrease in heart MDA (P< 0.05) was observed in diabetic rats with ω-3 fatty acids supplementation. Conclusion: Supplementation of vitamin A, E and C and ω-3 fatty acids was found to decrease lipid peroxidation to some ex¬tent in diabetic rats and they can be valuable candidates in the treatment of the complications of diabetes.